Flexible Plate in the Wake of a Square Cylinder for Piezoelectric Energy Harvesting—Parametric Study Using Fluid–Structure Interaction Modeling - Emmanuel Mbondo Binyet (Energies, 2020)
Piezoelectric energy harvesters can scavenge energy from their ambient environment in order to power low-consumption electronic devices. The last two decades have seen a growing interest towards vortex-induced vibration harvesters; most harvesters consist in rigid splitter plates oscillating at higher frequencies. The concept presented here is a low-frequency undulating flexible plate placed in the wake of a square cylinder. Piezoelectric patches can be placed at the plate surface to harvest the strain energy arising when the plate bends. The flapping pattern mimics an anguilliform swimming motion. There is a great need to establish correlation between wake generating bluff body size, plate dimensions and power output. Geometric parameters were investigated using water tunnel experiments, particle image velocimetry and fluid–structure interaction modeling. Results showed that for a given plate length and within a given freestream velocity range, there is a square cylinder diameter and a thickness that optimize the plate–wake interaction. Longer plates yield greater power output but have lower flapping frequencies. Additionally, the more frequent curvature changes occurring can result in charge cancellation among the piezoelectric cells. Consequently, the estimated conversion efficiency from mechanical strain to electricity is higher for shorter plates.